Nutritional Intervention for the Intestinal Development and Health of Weaned Pigs - Xiong, Xia; Tan, Bie; Song, Minho; Ji, Peng; Kim, Kwangwook; Yin, Yulong; Liu, Yanhong (Frontiers in Veterinary Science, 2019)
Weaning imposes simultaneous stress, resulting in reduced feed intake, and growth rate, and increased morbidity and mortality of weaned pigs. Weaning impairs the intestinal integrity, disturbs digestive and absorptive capacity, and increases the intestinal oxidative stress, and susceptibility of diseases in piglets. The improvement of intestinal development and health is critically important for enhancing nutrient digestibility capacity and disease resistance of weaned pigs, therefore, increasing their survival rate at this most vulnerable stage, and overall productive performance during later stages. A healthy gut may include but not limited several important features: a healthy proliferation of intestinal epithelial cells, an integrated gut barrier function, a preferable or balanced gut microbiota, and a well-developed intestinal mucosa immunity. Burgeoning evidence suggested nutritional intervention are one of promising measures to enhance intestinal health of weaned pigs, although the exact protective mechanisms may vary and are still not completely understood. Previous research indicated that functional amino acids, such as arginine, cysteine, glutamine, or glutamate, may enhance intestinal mucosa immunity (i.e., increased sIgA secretion), reduce oxidative damage, stimulate proliferation of enterocytes, and enhance gut barrier function (i.e., enhanced expression of tight junction protein) of weaned pigs. A number of feed additives are marketed to assist in boosting intestinal immunity and regulating gut microbiota, therefore, reducing the negative impacts of weaning, and other environmental challenges on piglets. The promising results have been demonstrated in antimicrobial peptides, clays, direct-fed microbials, micro-minerals, milk components, oligosaccharides, organic acids, phytochemicals, and many other feed additives. This review summarizes our current understanding of nutritional intervention on intestinal health and development of weaned pigs and the importance of mechanistic studies focusing on this research area.